2014
DOI: 10.1215/08992363-2346250
|View full text |Cite
|
Sign up to set email alerts
|

Making Citizens, Reassembling Devices: On Gender and the Development of Contemporary Public Sites of Repair in Northern California

Abstract: For the dozens of visitors to the 2012 East Bay Mini Maker Faire, many remarkable experiences were ripe for the taking. They could share in hands-on activities while attending a working group on outdoor mosaics, observing a robot-making demonstration, or sitting in on a make-your-own terrarium class. The activity in Studio One was no different: the energy was high and the action perplexing. Children clamored for a chance to use a Phillips-head screwdriver. Adults cut delicate wires and relayed stories of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 36 publications
2
41
0
1
Order By: Relevance
“…Regarding the gender of the organizers, mainly women arrange the events of the three case studies, but the observation in the network meeting of Repair Cafés in Germany hosted by the foundation Anstiftung & Ertomis showed that at least half of the organizers participating in this network event have been men. Regarding gender, the most significant pattern in respect of the actor constellations in the communicative figurations of Repair Cafés can be found in the group of helpers: while nearly exclusively men offer to repair media technologies, women volunteer to repair textiles; this finding goes along with the results of the study Daniela Rosner conducted in the USA (Rosner 2013).…”
Section: Actor Constellation In Repair Cafésmentioning
confidence: 55%
“…Regarding the gender of the organizers, mainly women arrange the events of the three case studies, but the observation in the network meeting of Repair Cafés in Germany hosted by the foundation Anstiftung & Ertomis showed that at least half of the organizers participating in this network event have been men. Regarding gender, the most significant pattern in respect of the actor constellations in the communicative figurations of Repair Cafés can be found in the group of helpers: while nearly exclusively men offer to repair media technologies, women volunteer to repair textiles; this finding goes along with the results of the study Daniela Rosner conducted in the USA (Rosner 2013).…”
Section: Actor Constellation In Repair Cafésmentioning
confidence: 55%
“…Feminist )ritques, pra)t)es and initatves have used ha)kathons, and other events with similar formats, to promote the equality of genders, ra)es or )lasses in the part)ipaton in te)hnology making. Their )entral )on)ern is the negle)ted viewpoints, experien)es and assumed in)apabilites with regards to te)hnology making at all levels, from s)hools and universites to professional (Fox et al, 2015;Maalsen and Perng, 2017;Rosner, 2014). Therefore, a key issue for them is whether programmer or maker subje)tvites, but not new te)hnologies, )an be developed.…”
Section: Neoliberal and Technocratic Rationality Critiquedmentioning
confidence: 99%
“…contexts. Research by Rosner and colleagues [19,20,21] has explored connections between repair, materiality and the longevity of artifacts; between repair and gendered conceptions of technology use and identity; and the material and ideological flows attached to repair work in global development projects. Jackson and Kang [8] have argued for links between repair, creativity and collaboration in artistic production, and their connection to questions of care and responsibility in human-object relations more generally.…”
Section: Background and Related Workmentioning
confidence: 99%